Challenges Facing the Integration of Information Communication and Technology in Teacher Education: A Case of Moi Teachers’ Training College - Baringo, Kenya - Sempele , N. L. Catherine; Moi, Louis L. Akim; Karei L. , Racheal (African Journal of Education,Science and Technology (AJEST), 2013)
The use of ICT in virtually every aspect of life today has made the computer an indispensable tool in the world. However, many teacher educators in Kenya are still not conversant with even the simple day-to-day computer operations. Kenya plans to achieve newly industrialized status by the year 2020 and to do so most of its citizenry needs to be computer literate. The study looked at the challenges facing the integration of ICT in teacher education at Moi Teachers’ Training College – Baringo, Kenya. The objectives of the study were to investigate the need for ICT at the college, the availability of ICT facilities and to establish the frequency of use of ICT facilities by teacher educators during classroom instruction. This was meant to establish the possible reasons for slow integration of ICT in training by teacher educators at the college and thus offer possible recommendations aimed at improving ICT integration in teacher training. The research was a descriptive survey study. The researchers purposively selected all 38 members of the teaching staff as participants because they possessed the required information. Self administered questionnaires were used to collect data from the respondents. Descriptive statistics was used to analyze the data. Frequency and percentage tables were generated from these summaries for ease in comprehension and interpretation. The study established that more than half of the trainers have not been trained on ICT with the majority citing this as the main hindrance to effective integration of ICT in teacher education. The mobile phone was the most popular ICT facility for the trainers. The correlation analysis established no significant relationship between the availability of ICT resources and frequency of their use in classroom instruction. The researchers recommend that teacher trainers in colleges be trained on ICT use